2019
DOI: 10.1039/c9cp04068d
|View full text |Cite
|
Sign up to set email alerts
|

Molecule-level graphdiyne coordinated transition metals as a new class of bifunctional electrocatalysts for oxygen reduction and oxygen evolution reactions

Abstract: Graphdiyne (GDY) could provide a unique platform for synthesizing uniform single-atom catalysts (SACs) with high catalytic activity toward oxygen reduction (ORR) and oxygen evolution (OER) reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 77 publications
0
38
0
Order By: Relevance
“…1,4,7 The ORR take place during discharging, oxidizing the metal at the counter electrode, while the OER occurs during charging, oxidizing the metal at the counter electrode. 4,8 ORR involves numerous consecutive steps, including oxygen diffusion from the atmosphere to the catalyst surface, oxygen adsorption on the catalyst surface, and electron transfer from the anode to the oxygen molecules on the cathode surface to form the discharge product. 9 To be highly efficient, energy storage devices, or metalair batteries required fast ORR, also, highly-reversible to regenerate oxygen molecules during the charging process where OER takes place.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,7 The ORR take place during discharging, oxidizing the metal at the counter electrode, while the OER occurs during charging, oxidizing the metal at the counter electrode. 4,8 ORR involves numerous consecutive steps, including oxygen diffusion from the atmosphere to the catalyst surface, oxygen adsorption on the catalyst surface, and electron transfer from the anode to the oxygen molecules on the cathode surface to form the discharge product. 9 To be highly efficient, energy storage devices, or metalair batteries required fast ORR, also, highly-reversible to regenerate oxygen molecules during the charging process where OER takes place.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Ma et al designed a series of GDY-supported TM SACs for the OER. 144 The positive binding energy (E b ) and suitable energy difference (DE b ) between E b and cohesive energy (D-F) the free energy diagrams of Ni@GDY, Pd@GDY, and Pt@GDY in alkaline media for the OER; (G-I) the optimized adsorption structures of OOH, O and OH on Ni@GDY, Pd@GDY and Pt@GDY monolayers (the gray, red, and white balls represent C, O, and H atoms, respectively); (J-L) the top view and side view of the charge density difference of O/Ni@GDY, O/Pd@GDY, and O/Pt@GDY; (M-O) the spin density of O/Ni@GDY, O/Pd@GDY, and O/Pt@GDY (yellow and blue regions represent charge accumulation and depletion or spin-up and spin-down states and the isosurface level is 0.02 e ÅÀ3 ). Reproduced with permission.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…It is well known that each element has its own chemical properties. When the single metal atom is considered to be the active site, different single metal atoms featured with different atomic structures may demonstrate different activities [167][168][169][170][171][172]. Duan et al [102] reported an approach using graphene oxide to fabricate atomic 3d metal atoms embedded in nitrogen-doped holey graphene frameworks (M-NHGFs).…”
Section: The Inherent Element Propertymentioning
confidence: 99%